MENGGAGAS âDESA INFORMASIâ DI PERBATASAN - Arifianto, Somo (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2014)
The pattern of communication and social structure on villagers in borderline of West Kalimantan, generally are more dominant to be influence and construct by media and culture of Malaysia. Those conditions influence the response of people towards government policy and access to information through the communications infrastructure on the border. The purpose of the research are to explain, the responses of people, and factors that influence the integration of information technology infrastructure, social communication institution, and community resources as a supporting component of âDesa Informasiâ. This qualitative research is using single case study methodology with emic perspective. Primary data are gathered from FGD and interview with informant. Secondary data are from literature study, document and other publicity material. The technique to process the data are using classification based on the structure of the theme, summarized and analyzed. Unit analysis of social communication institution. The results showed that: the villagers of Jagoi still not optimal in responding to the idea of rural development information, because they never receive information about the village concept comprehensively through socialization. Whereas the factors that influence the development of âDesa Informasiâ in rural Jagoi, are because the ICTâs infrastructure and internet, institutions of social communication, community resources, and its uses to access information as communityâs needs that had economic value to support the idea of âDesa Informasiâ development, which still not integrated yet.